Multibeam bathymetry raw data (Kongsberg EM712 entire dataset) of RV MARIA S. MERIAN during cruise MSM126 - Julian B Stauffer; Henk-Jan T Hoving; Iason-Zois Gazis; Jochen Mohrmann; Mareike Kampmeier; Mario Enrique Veloso-Alarcón; Mia Schumacher; Jan Dierking (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV MARIA S. MERIAN during cruise MSM126 using a Kongsberg EM 712 multibeam echosounder. The expedition took place during 09.02.2024 - 04.03.2024 from Funchal (Portugal) to Las Palmas (Gran Canaria). Data were recorded in the Portuguese EEZ and outside. The aims of MSM126 include the documentation of biodiversity, food web relations and the role of pelagic fauna in transferring carbon to the seafloor off Madeira Island. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and are according to the FAIR principles.